Impact of counterclockwise rotation of the right middle lobe following right upper lobectomy. (18th December 2021) - Koike, Sachie; Eguchi, Takashi; Matsuoka, Shunichiro; Takeda, Tetsu; Miura, Kentaro; Shimizu, Kimihiro; Hamanaka, Kazutoshi
Abstract: OBJECTIVES: Following right upper lobectomy, the right middle lobe may shift towards the apex and rotate in a counterclockwise direction with respect to the hilum. This study aimed to investigate the incidence and clinical impact of middle lobe rotation in patients undergoing right upper lobectomy. METHODS: From January 2014 to November 2018, 82 patients underwent right upper lobectomy at our institution for lung cancer using a surgical stapler to divide the minor fissure. Postoperative computed tomography scans evaluated the counterclockwise rotation of the middle lobe, in which the staple lines placed on the minor fissure were in contact with the major fissure of the right lower lobe (120° counterclockwise rotation). Clinicoradiological factors were evaluated and compared between patients with and without middle lobe rotation. We also reviewed surgical videos in patients with middle lobe rotation to evaluate the position of the middle lobe at the end of surgery. RESULTS: Nine patients had a middle lobe rotation (11%), where 1 patient required surgical derotation. Patients with middle lobe rotation were significantly associated with more frequent right middle lobe atelectasis and severe postoperative complications compared with those without rotation. A surgical video review detected potential middle lobe rotation at the end of the surgery. CONCLUSIONS: Middle lobe rotation without torsion following right upper lobectomy is not rare, and it is associated with adverse postoperative courses. Careful positioning of the right middle lobe at the end of surgery is warranted to improve postoperative outcomes. Abstract : Lobectomy is the standard surgical procedure for early stage lung cancer [1].